Helicobacter pylori infection and staple-line leak in patients with class III obesity undergoing laparoscopic sleeve gastrectomy: a retrospective study - Hani Tamim; Albaraa H Kazim; Fahad Y Bamehriz; Aldanah M Althwanay; Abdullah Aldohayan; Al-Bandari Zamil Abdullah; Bandar AlShehri; Rakan Masoud AlTuwayr; Habeeb I A Razack; Fahad Alsohaibani; Saleh A Alqahtani (BMJ Open Gastroenterology)
Objective Globally, over 50% of the population is affected by Helicobacter pylori, yet research on its prevalence and impact in patients with obesity undergoing laparoscopic sleeve gastrectomy (LSG) is inconclusive. This study aimed to assess the prevalence of H. pylori infection in individuals with obesity undergoing LSG, evaluate the percentage of postoperative staple-line leaks, and explore the potential link between H. pylori infection and staple-line leaks.Methods This retrospective analysis assessed adult patients with class III obesity who underwent LSG between 2015 and 2020 at a tertiary care hospital in Riyadh, Saudi Arabia. Patient characteristics with and without postoperative staple-line leaks were compared, exploring the link between H. pylori infection and these leaks.Results Of the 2099 patients (mean age, 34.7±12.2 years; female, 53.5%) included, 35% had H. pylori infection and 2% experienced post-LSG staple-line leaks. Patients with H. pylori were older (36.1±11.8 vs 34.0±12.3 years, p<0.0001). Patients with leaks were older, mostly male, and had higher body mass index (p<0.05). However, only 29% of those with leaks were H. pylori-positive. A non-significant association was found between H. pylori infection and staple-line leaks (adjusted OR 0.73, 95% CI 0.33 to 1.60, accounting for age, body mass index, and sex).Conclusions Although over one-third of patients with class III obesity undergoing LSG had H. pylori infection, a non-significant association was observed with post-LSG staple-line leaks, suggesting routine preoperative H. pylori screening may not be necessary.